Diabetes Mellitus as the Main Factor of Restenosis: Literature Review - Sabila Nisak; Abu Bakar; Laily Hidayati (Universitas Airlangga, 2021)
Background: Patients with cardiac stent have been risk of restenosis. Several studies suggest that diabetes mellitus is the factor that most consistently increases the risk of restenosis. This requires further research with the literature review to analyze the continuity of the journals found.Methods: A literature review searched based on PRISMA, by the process of identification, screening, eligibility, and included. Journals are identified based on their focus and results. Then screening by analyzing the design, samples, variables, instruments, methods and results. Then assessed for their eligibility using The Joanna Briggs Institute (JBI) Critical Appraisal.Results: The total number of journals that reviewed in this study is 15 journals. Six journals stated DM as a restenosis factor, two journals stated BMI as the main factor, four journals mentioned other factors and two journals denied DM was a predictor of restenosis.Conclusion: The results of 15 journals that reviewed, diabetes mellitus was a factor that appeared consistently and had a role in the incidence of restenosis from lifestyle factors or disease history.